How important are the international financial market imperfections for the foreign exchange rate dynamics: A study of the sterling exchange rate - Xue Dong; Patrick Minford; David Meenagh (Cardiff University, Cardiff Business School, 2018)
The UK has been a net debtor over the past two decades and the sterling exchange rates are sensitive to any chaos that might occur in the Financial market. This paper examines the importance of the inter-national financial imperfections in the sterling exchange rate dynamics. We build a small open economy DSGE model with the constrained international financial institutions that intermediate capital flows, and derive tractable analytical solutions. The constraint works to introduce a wedge between lending and borrowing rates, which compensates financiers for their currency risk-taking. The model has been estimated by using a simulation-based Indirect Inference approach, which provides a natural framework for testing the hypothesis implied by the model. We find that the model cannot be rejected by the UK data. Shocks to financial forces are the main driving forces behind the large and sudden depreciation of the Sterling exchange rates in the aftermath of the collapse of Lehman Brothers and the Brexit vote. Furthermore, the optimal policy rules have been proposed.
Keywords: E63; F31; F34; F41; F47; 330; Small open economy DSGE model; International financial imperfections; Sterling exchange rates; Indirect Inference; Crisis; Policy rules